Comparison between a Computational Seated Human Model and Experimental Verification Data. Issue 4 (11th November 2014) - Olesen, Christian G.; de Zee, Mark; Rasmussen, John
Abstract : Sitting-acquired deep tissue injuries (SADTI) are the most serious type of pressure ulcers. In order to investigate the aetiology of SADTI a new approach is under development: a musculo-skeletal model which can predict forces between the chair and the human body at different seated postures. This study focuses on comparing results from a model developed in the AnyBody Modeling System, with data collected from an experimental setup. A chair with force-measuring equipment was developed, an experiment was conducted with three subjects, and the experimental results were compared with the predictions of the computational model. The results show that the model predicted the reaction forces for different chair postures well. The correlation coefficients of how well the experiment and model correlate for the seat angle, backrest angle and footrest height was 0.93, 0.96, and 0.95. The study show a good agreement between experimental data and model prediction of forces between a human body and a chair. The model can in the future be used in designing wheelchairs or automotive seats.